PATTERN OF URINARY TRACT FINDINGS ON HELICAL COMPUTED TOMOGRAPHY IN CASES OF URETEROLITHIASIS: Cases of Ureterolithiasis - Khan, Lt Col Khalid Rahim; Khalid, Ambreen; Mirza, Tariq Mahmud; Ali, Muhammad Zeeshan (Pakistan Armed Forces Medical Journal, 2012)
Objectives: To determine the pattern of urinary tract changes in cases of ureterolithiasis as detected on helical computed tomography.Study Design: Descriptive study.Settings: Radiology Department Combined Military Hospital Lahore from Jun 2007 to Jan 2008.Material and Methods: Thirty patients with proven ureterolithiasis on IVU were included. All these patients underwent non contrast enhanced helical computed tomography (CT) scan. Data was analyzed for both quantitative as well as qualitative data and expressed as mean with standard deviation and percentages respectively.Results: All 30 patients had ureteric calculi. Among our study group the frequency expressed as percentages of various secondary signs of ureterolithiasis were hydroureter 25 (83.33%), hydronephrosis of the affected kidney in 23 (76.67%), nephromegaly 16 (53.33%), periureteral edema 19 (63.33%), perinephric stranding 21 (70%), a difference in attenuation between the kidneys 25 (83.33%) while soft tissue rim sign was present in 14 (46.67%) patients. Only one patient lacked the secondary signs.Conclusion: Establishing the pattern of secondary urinary tract findings enables a brisk diagnosis in cases of obstructive ureterolithiasis, thus improving the diagnostic capabilities as well as patient outcome.